780 Treatment of life-threatening digoxin toxicity with digoxin immune fab antibody: findings from the UK DigiFab®patient registry. Issue 3 (21st February 2022) - Thomas, Emma; Tomlinson, Sam; Thomas, Siwan; Ward, Suzanne; Daugherty, Claire; Gallardo, Eva; Hill, Christon
Abstract : Aims/Objectives/Background: Digoxin continues to play an important role in the management of atrial fibrillation (AF) and heart failure. Toxicity due to acute over-ingestion of digoxin is generally mild and manageable but can be life-threatening. 1 Digoxin immune Fab (DIF; DigiFab ® ) is the mainstay of treatment for life-threatening digoxin toxicity (LTDT). We report findings on efficacy and safety of DIF from the UK DigiFab Patient Registry. Methods/Design: This prospective, observational study was a post-authorisation requirement from the MHRA. Physicians in all UK hospitals using DIF were invited to submit data for any patient who received DIF for LTDT. All AEs were followed-up according to Good Pharmacovigilance Practice. Results/Conclusions: Between April 2012 and June 2017, 94 patients were enrolled; 10 were excluded (off-label DIF, n=2; outcome not recorded, n=8). Patients were typically elderly (mean: 81 years) and >80% cases involved chronic vs acute toxicity. Most frequently reported symptoms were bradycardia (74%), abnormal mental status/visual disturbance (40%), hyperkalaemia (33%) and gastrointestinal effects (32%). Other cardiac arrhythmias included 2nd/3rd degree heart block (19%), AF (13%), asystole (5%) and ventricular tachycardia (5%); 85% of patients experienced ≥1 arrhythmia. DT resolved in 57 (67.9%) and persisted in 24 (28.6%) patients at the time of reporting. For the remaining 3 (3.6%) patients, the recorded outcome was death. 7 patients reported adverse drugs reactions, including death (n=3) and AF, bradycardia, cardio-respiratory arrest, acute renal failure, cellulitis and hypoglycaemia (all n=1). No cause was reported/established for the 3 deaths and so these were conservatively assessed as possibly related to DIF but were most likely complications of underlying medical conditions. The results were consistent with earlier reports with digoxin-specific antibody Fab fragments, 2 with DIF highly effective in resolving LTDT in a real-world setting. References: Gummin DD, et al. Clin Toxicol 2020;58 :1360–541. Schaeffer TH, et al. J Am Osteopath Assoc 2010;110 :587–92.